A Bioprinted Cardiac Patch Composed of Cardiac‐Specific Extracellular Matrix and Progenitor Cells for Heart Repair. Issue 23 (31st October 2018) - Bejleri, Donald; Streeter, Benjamin W.; Nachlas, Aline L. Y.; Brown, Milton E.; Gaetani, Roberto; Christman, Karen L.; Davis, Michael E.
Abstract: Congenital heart defects are present in 8 of 1000 newborns and palliative surgical therapy has increased survival. Despite improved outcomes, many children develop reduced cardiac function and heart failure requiring transplantation. Human cardiac progenitor cell (hCPC) therapy has potential to repair the pediatric myocardium through release of reparative factors, but therapy suffers from limited hCPC retention and functionality. Decellularized cardiac extracellular matrix hydrogel (cECM) improves heart function in animals, and human trials are ongoing. In the present study, a 3D‐bioprinted patch containing cECM for delivery of pediatric hCPCs is developed. Cardiac patches are printed with bioinks composed of cECM, hCPCs, and gelatin methacrylate (GelMA). GelMA‐cECM bioinks print uniformly with a homogeneous distribution of cECM and hCPCs. hCPCs maintain >75% viability and incorporation of cECM within patches results in a 30‐fold increase in cardiogenic gene expression of hCPCs compared to hCPCs grown in pure GelMA patches. Conditioned media from GelMA‐cECM patches show increased angiogenic potential (>2‐fold) over GelMA alone, as seen by improved endothelial cell tube formation. Finally, patches are retained on rat hearts and show vascularization over 14 d in vivo. This work shows the successful bioprinting and implementation of cECM‐hCPC patches for potential use in repairing damaged myocardium. Abstract : Therapies such as injectable human cardiac progenitor cells (hCPCs) and cardiac extracellular matrix (cECM) have shown improvements in treating damaged myocardium, but are limited by poor retention and functionality. Herein, cardiac patches composed of both hCPCs and cECM are created through 3D bioprinting and allow for the release of proregenerative paracrine factors toward the damaged myocardium for pediatric patients.